Developing The Quality of Traditional Islamic Boarding School Using The Total Quality Management Model - Jajuli Jajuli; Khaerul Wahidin; Adi Fahrudin (Asian Social Work Journal, 2022)
This study aims to reveal data related to efforts to develop the quality of traditional Islamic boarding schools (pesantren) using the TQM method at the Kebon Jambu Ciwaringin Islamic Boarding School, Cirebon Regency. This study uses qualitative research methods to obtain data through observation, interviews, and documentation. The results of the research study show that by applying the TQM model the quality of education at the Kebon Jambu Islamic boarding school is well maintained with evidence of inputs being carried out through effective and efficient processes and outputs produced through these good educational processes. This boarding school can produce graduates who are proficient in religious knowledge and skills in other fields. Besides that, the legality of education has been recognized by both the Muslim community and the government. Second, in implementing the TQM model to improve the quality of education, the Kebon Jambu Islamic Boarding School makes several programs that are structured and implemented by all stakeholders of the boarding school effectively and efficiently. This achievement was supported by Ustadz competence, adequate infrastructure, and good financing management.